Analysis of Employee Commitment to Employee Performance (Study at KJA PT. Eriadi Fatkhur Rokhman) - Aulia Rahmah; Juliana Nasution (Journal of Management and Business Innovations, 2022)
This study aims to determine employee commitment to improving performance at the accounting service office of PT. Eriadi Fathur Rohman. This research was motivated by the fact that we saw employees of KJA PT. The small number of Eriadi Fathur Rohman is one of the sources of the company's success in carrying out its duties. This study uses a qualitative method with a descriptive approach. The data collection techniques used are interviews and documentation with manager and employee informants who are in the Accounting Services Office of PT. Eriadi Fatkhur Rokhman. The results showed that the commitment of the employees of the Accounting Services Office of PT. Eriadi Fatkhur Rokhman is very good at improving performance because the commitment of his employees belongs to the type of affective commitment.Keywords: affective commitment, employee commitment, employee performance